2022
DOI: 10.1111/jpn.13784
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic mixture (Bacillus subtilis and Bacillus licheniformis) a potential in‐feed additive to improve broiler production efficiency, nutrient digestibility, caecal microflora, meat quality and to diminish hazardous odour emission

Abstract: This research aimed to assess the impact of probiotic supplementation in the broiler diet on growth performance, nutrient utilization, noxious gas emissions, excreta micromiota and meat quality. One thousand six hundred and twenty male Ross 380 broilers (one‐day‐old, body weight, 42 ± 0.5 g and 5‐week trial) were arbitrarily chosen and assigned to three nutritive treatments (basal diet and basal diet included with 0.1%, and 0.2% probiotic mixture [Bacillus subtilis 7.0 × 107 cfu/g, Bacillus licheniformis 4.1 ×… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 50 publications
0
10
0
1
Order By: Relevance
“…The pH levels of every breast meat specimen were recorded and analyzed twice using a pH meter (Testo SE & Co., KGaA, Testo 205, Lenzkirch, Germany). By using the techniques followed by Biswas et al (2022) , the water-holding capacity ( WHC ), cooking loss, and drip loss were estimated.…”
Section: Methodsmentioning
confidence: 99%
“…The pH levels of every breast meat specimen were recorded and analyzed twice using a pH meter (Testo SE & Co., KGaA, Testo 205, Lenzkirch, Germany). By using the techniques followed by Biswas et al (2022) , the water-holding capacity ( WHC ), cooking loss, and drip loss were estimated.…”
Section: Methodsmentioning
confidence: 99%
“…Researchers have been seeking more sustainable alternatives to antibiotics for decades, and probiotics and prebiotics could be a suitable one (139). Probiotics or/and prebiotic supplementation enhanced the immunity of the animal, increased feed digestibility, promoted the growth and reproductive performance, improved the yield and quality of meat, milk, and eggs, increased the content of free amino acids, eicosapentaenoic acid (EPA), docosahexaenoic acid (DHA), superoxide dismutase, glutathione peroxidase, decreased the content of saturated fatty acids, triglyceride, and cholesterol (140)(141)(142)(143)(144)(145)(146), and reduced the noxious gas emission including ammonia and sulfuretted hydrogen (147) and harmful substance accumulation such as chromium (146). Our study in food animals also found that feeding certain Lactobacillus strains fermented feed not only increased feed conversion ratio, decreased noxious gas in feces, and reduced aggressive behaviors, but also lesson the cholesterol in eggs and meat and increased the lean body mass and content of EPA and DHA.…”
Section: The Industrialization Of Gut Microbiota and Increase Of Dise...mentioning
confidence: 99%
“…Simultaneously, identical pH levels for each specimen were recorded using a pH meter (Testo205, Testo). The water holding capacity (WHC), cooking loss and drip loss were calculated by the procedure of Biswas et al (2022).…”
Section: Organ Weight and Meat Quality Analysismentioning
confidence: 99%